2020
DOI: 10.1039/d0na00107d
|View full text |Cite
|
Sign up to set email alerts
|

Bio-electrostatic sensitive droplet lasers for molecular detection

Abstract: A bioelectrostatic responsive microlaser based on liquid crystal droplets was developed and explored for ultrasensitive detection of negatively charged biomolecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 29 publications
0
53
0
Order By: Relevance
“…In addition, the position of the droplets inside a given medium can be controlled using optical trapping, magnetic fields, electrodynamic ion traps (Paul traps) and ultrasonic waves 69 , 71 75 . Droplet-based resonators with liquid crystals as an integral component within the droplet offer an opportunity for tuning and tailoring droplet properties, such as the orientation of the LCs using electric fields 6 , 54 . Tuning of the droplet-based sensor can improve its sensitivity limits and makes it capable of sensing biomolecules with negative charges 6 .…”
Section: Microdroplet Resonators As Active Cavities In Biosensingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the position of the droplets inside a given medium can be controlled using optical trapping, magnetic fields, electrodynamic ion traps (Paul traps) and ultrasonic waves 69 , 71 75 . Droplet-based resonators with liquid crystals as an integral component within the droplet offer an opportunity for tuning and tailoring droplet properties, such as the orientation of the LCs using electric fields 6 , 54 . Tuning of the droplet-based sensor can improve its sensitivity limits and makes it capable of sensing biomolecules with negative charges 6 .…”
Section: Microdroplet Resonators As Active Cavities In Biosensingmentioning
confidence: 99%
“…Droplet-based resonators with liquid crystals as an integral component within the droplet offer an opportunity for tuning and tailoring droplet properties, such as the orientation of the LCs using electric fields 6 , 54 . Tuning of the droplet-based sensor can improve its sensitivity limits and makes it capable of sensing biomolecules with negative charges 6 . However, fabrication and tuning of LC droplets is complicated; therefore, their use for in vivo applications has not yet been demonstrated.…”
Section: Microdroplet Resonators As Active Cavities In Biosensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the interactions between LC molecules and biological targets, LC is high-sensitive to molecules anchoring and electrostatic force at interfaces. During the past several years, the LC biosensing platform has been explored in various forms, such as thin films [1][2][3][4][5] and microdroplets [6][7][8][9][10][11][12]. The orientation transition of LC molecules from homeotropic to planer (or from radial to bipolar) induced by biomolecules changing can be observed under a polarized optical microscope (POM) by the naked eye.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microlasers, as an emerging technology, attract widespread attention in the biomedical and biological fields. LC microsphere based whispering gallery mode (WGM) lasers, with the properties of high Q factor and compact cavities, have been demonstrated that it is a more sensitive method for biomolecules detection [7,9,[13][14][15]. The dye-doped LC droplet, as a microcavity, can generate the WGM laser and is used to be a sensing probe as well.…”
Section: Introductionmentioning
confidence: 99%